Delayed orbital floor implant complications: Case report and review of the literature - Brian Soetikno; Steven Losorelli; Chaow Charoenkijkajorn; Jayakar V. Nayak; Natalie A. Homer (American Journal of Ophthalmology Case Reports, 2024)
Purpose: Foreign body reaction to non-absorbable alloplastic orbital implants utilized for bony reconstruction are infrequently documented in the literature. We present the workup and surgical management of a giant cystic mass encapsulating a patient's alloplastic orbital implant, which was ultimately deemed to be a result of foreign body reaction. Observations: A 41-year-old male patient with distant history of a right orbital floor fracture had undergone repair with the placement of a nylon foil implant. The patient presented twenty years later with progressive ipsilateral globe proptosis and was found to have a giant inferior orbital cyst. Surgical exploration and removal of the implant and capsule were performed. Histopathology confirmed a delayed foreign body reaction around the patient's alloplastic implant. Conclusions: Alloplastic implants may result foreign body reaction and cyst encapsulation as a delayed complication.